Long-term monitoring of a flagship bird species in agroecosystems enhances stakeholder engagement in biodiversity conservation - Andrea Rizzardi Orlandi; Roberto Ambrosini; Diego Rubolini; Andrea Romano; Luigi Orsi; Mattia Brambilla; Alessandra Costanzo (Global Ecology and Conservation, 2024)
Conservation efforts are needed in the face of the rapid decline in farmland birds over the past decades. While existing conservation strategies have shown limited success, there is a growing recognition of the role of farmers as primary stakeholders in agroecosystems conservation. We applied the ''Human Dimension'' approach, which emphasizes the importance of human perspectives on wildlife conservation, to assess whether a long-term monitoring project of barn swallows Hirundo rustica, ongoing since 1999, has heightened farmers’ awareness regarding biodiversity protection. Indeed, while monitoring serves to track population trends and understand the factors influencing species dynamics, it also provides opportunities for interaction between researchers and farmers. Through in-person administration of the questionnaire, we investigated the impact of the barn swallow monitoring project on farmers’ environmental consciousness in terms of their perceptions of the environment, knowledge about priority habitats for biodiversity, and preferences for environmental awareness strategies. Subsequently, we investigated whether environmental consciousness and the participation in the barn swallow monitoring project translated into their inclination to implement costless actions for barn swallow conservation. Our findings suggest that the barn swallow monitoring project may not have enhanced farmers’ environmental consciousness. However, a higher environmental consciousness and the engagement in the barn swallow monitoring project were associated to a greater willingness to undertake actions in support of barn swallows. This study highlights the potential of long-term projects in fostering the conservation of charismatic species through establishing a mutual trust between farmers and researchers over years of monitoring, with cascading benefits for the barn swallows.